Tanggung jawab sosial dan kinerja perusahaan: Peran moderasi dari ukuran perusahaan - Liliana Inggrit Wijaya; Lady Safitri Sugiarto; Bertha Silvia Sutejo (Universitas Kristen Maranatha, 2024)
Social responsibility (SR) is a way for companies to fulfill their commitments to the public. If the companies have a positive public perception, investors will be more interested in purchasing stocks in the capital market, increasing the price. Therefore, social responsibility is expected to improve firm value, as measured by Tobin’s Q, and this study aims to prove the effect of SR on firm value moderated by its size and controlled by leverage and intensity of research and development. The research samples consist of 65 non-financial companies listed on the Indonesia Stock Exchange from 2019 to 2023 and are taken utilizing a purposive sampling technique. Acting as the data analysis method is the panel data regression model. The regression coefficient testing result displays that the interaction between SR and size positively influences company value. As the control variable, leverage negatively affects this value; however, research and development intensity has no influence. This research implies that SR is an effective strategy for improving the firm’s value as its size elevates by managing sustainable relationships with stakeholders amid rampant environmental issues.